Pharmacological Profile and Therapeutic Potential of Sungkai Plant (Peronema canescens Jack.): An Emerging Indonesian Herbal Medicine - Yasmiwar Susilawati; Sri Adi Sumiwi; Okta Nama Putra; Asep Kokom (Fakultas Farmasi Universitas Andalas, 2024)
This study aimed to summarize the pharmacological activities of the sungkai plant (Peronema canescens Jack.) as a potential Indonesian herbal medicine. A literature review was conducted using Google Scholar and Scopus, with keywords such as